Analisis Current Ratio dan Profit Margin terhadap Pertumbuhan Laba Perusahaan Terdaftar Bursa Efek Indonesia - Juliana Juliana; Dian Lestari Siregar (Universitas Batanghari Jambi, 2022)
The goal of the following study is to look at the impact of the Current Ratio and Profit Margin variables upon that Profit Growth of manufacturing company quoted on the Indonesia Stock Exchange for the 2016–2020 period. The types of data are secondary sources, purposive sampling technique and quantity method and the data is processed using the IBM Statitic version 23 program. Its population is 30 as well as the sample is 8 entities. From the research, the t-test shows that the current ratio slightly has a significant influences of profit growth. Tcount is ,-2,473> ttable 2,026 and the sig level is 0,018 t table 2,026 and a sig level of 0,006 < 0> 3.25 and the sig level is 0.014<0,05. R square 0,207 or 20,7% is influced by Current Ratio and Net Profit Margin, with the remaining 79,3% impated through other variable that not researched by the researcher.